2019
DOI: 10.1002/adsu.201900101
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine Nanoparticle Doped Nanofluid for Solar Thermal Energy Collector Efficiency Increase

Abstract: Polydopamine can form black nanoparticles and has recently been gaining attention due to its extraordinary heating properties upon excitation with light. Herein, polydopamine hybrid nanoparticles are synthesized in different sizes and subsequently added to a solar fluid to analyze heating ability. The solar fluids with the differently sized hybrid polydopamine particles are compared to a solar fluid containing food coloring (i.e., micrometer‐sized soot particles, similar to India Ink) and silver nanoparticles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The coated dye-sensitised solar cells were found to perform with a power conversion efficiency of 1.2% [58]. PDA was also investigated for their use as a solar fluid dopant in the generation of solar thermal energy as an alternative to photovoltaics [59]. To this end, PDA nanoparticles, consisting of PDA and bovine serum albumin, were added to a so-called solar fluid whose efficiency was then assessed in a 3D-printed flow circuit using a solar simulator as an irradiation source [59].…”
Section: Pda For Adhesive and Energy-related Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The coated dye-sensitised solar cells were found to perform with a power conversion efficiency of 1.2% [58]. PDA was also investigated for their use as a solar fluid dopant in the generation of solar thermal energy as an alternative to photovoltaics [59]. To this end, PDA nanoparticles, consisting of PDA and bovine serum albumin, were added to a so-called solar fluid whose efficiency was then assessed in a 3D-printed flow circuit using a solar simulator as an irradiation source [59].…”
Section: Pda For Adhesive and Energy-related Applicationsmentioning
confidence: 99%
“…PDA was also investigated for their use as a solar fluid dopant in the generation of solar thermal energy as an alternative to photovoltaics [59]. To this end, PDA nanoparticles, consisting of PDA and bovine serum albumin, were added to a so-called solar fluid whose efficiency was then assessed in a 3D-printed flow circuit using a solar simulator as an irradiation source [59]. It was found that the addition of the NPs indeed increased the efficiency of the solar fluid up to 280% compared to the plain solar fluid [59].…”
Section: Pda For Adhesive and Energy-related Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This challenge can be overcome by incorporating fluids with high thermal conductivity as the working fluid in the solar collectors to help y fast thereby increasing their ability to absorb solar energy. The working fluids suitable for enhancing the efficiency of these [61][62]. A study on direct absorption solar collectors based on (SiCethylene glycol) hybrid nanofluids reported a 97.3% improvement in solar-thermal conversion efficiency at 1 wt% hybrid nanofluid concentration.…”
Section: Solar Energy Collectionmentioning
confidence: 99%